Dietary 23–hydroxy ursolic acid protects against atherosclerosis and obesity by preventing dyslipidemia-induced monocyte priming and dysfunction. (August 2018) - Nguyen, Huynh Nga; Ahn, Yong Joo; Medina, Edward Antonio; Asmis, Reto
Abstract: Background and aims: We demonstrated that dietary ursolic acid (UA) reduces atherosclerotic lesion size and improves kidney function in diabetic mice. Based on structure-function analyses of naturally occurring UA analogs, we synthesized 23-hydroxy ursolic acid (23-OHUA), a compound with structural features predicted to enhance its bioavailability and anti-atherogenic properties compared to UA. The goal of this study was to determine the anti-obesogenic and atheroprotective properties of 23-OHUA and its mechanism of action. Methods: We performed chemotaxis assays to determine IC50 of phytochemicals on primed THP-1 monocytes. We fed 12-week old female LDLR −/− mice a high-fat diet (HFD) or a HFD supplemented with either 0.05% UA or 0.05% 23-OHUA, and measured monocyte priming, weight gain and atherosclerotic lesion size after 6 and 20 weeks. Results: Both dietary UA and 23-OHUA prevented dyslipidemia-induced loss of MKP-1 activity, and hyper-chemotactic activity, hallmarks of blood monocytes priming and dysfunction, but they did not affect plasma lipids or blood glucose levels nor WBC and monocyte counts. After 20 weeks, mice fed 23-OHUA showed 11% less weight gain compared to HFD-fed control mice and a 40% reduction in atherosclerotic plaque size, whereas UA reduced lesion size by only 19% and did not reduce weight gain. Conclusions: Dietary 23-OHUA reduces weight gain and attenuates atherogenesis in mice by protecting monocytes against metabolic stress-induced priming and dysfunction. Based on its mechanism of action, 23-OHUA may represent a novel therapeutic approach for the prevention and treatment of obesity and atherosclerosis. Highlights: Dietary 23-hydroxy ursolic acid reduces weight gain in atherosclerosis-prone mice fed a high-fat diet by 11%. Dietary 23-hydroxy ursolic acid reduces atherosclerotic plaque size in atherosclerosis-prone mice fed a high-fat diet by 40% without affecting plasma lipid, lipoprotein or glucose levels. 23-Hydroxy ursolic acid prevents monocyte priming and dysfunction induced by dyslipidemia and hyperglycemia, which may account for its anti-obesogenic and atheroprotective properties.